Famine As an Instrument of Nazi Occupation Policy in Ukraine, 1941-44 - Lysenko, Oleksandr; Zabolotna, Tetiana; Maievs'kyi, Oleksandr (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
The article examines a range of questions tied to Nazi Germany’s socio-economic policies in occupied Ukraine during World War II. In line with implementing the General Plan “Ost,” the top leadership of the Third Reich intended to cleanse the “eastern territories” of its “superfluous” population for German colonization. As contained in the “Principles of Economic Policy in the East,” these directives provided for the physical extermination of tens of millions of people in various ways, as well as the deportation of part of the indigenous population to remote areas. Ukraine’s economic exploitation was built in such a way that it doomed the local urban and rural societies to a miserable, half-starved existence. The systematic seizure of food for the needs of the Wehrmacht, the Reich, and its allies made the death of the inhabitants of the occupied lands only a matter of time. The instrumentalization of terror by famine was manifested, on the one hand, by the creation of special structures that requisitioned food resources, and on the other by establishing norms of food supplies that were below the minimal needs for existence. As well, the strict regulation of trade set limits to the sources of food products that could be brought to the cities. This caused mass starvation. The deaths and the diseases that followed created hundreds of thousands of victims among Ukrainians.